FACTORS INFLUENCING THE ADOPTION OF LIQUID FERTILIZER AMONG MAIZE FARMERS IN WESTERN AGRICULTURAL ZONE OF BAUCHI STATE, NIGERIA - Paul, R. B.; Garba, M.; Mele, A. M. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the factors influencing the adoption of liquid fertilizer among maize farmers in the Western Agricultural Zone of Bauchi State, Nigeria. A multistage sampling technique was used to select 201 maize farmers across three Local Government Areas namely Bauchi, Toro, and Tafawa Balewa. Primary data were obtained through structured questionnaires and analyzed using descriptive statistics and binary logit regression model. The results revealed that majority (78.1%) of the respondents were male and 85.6% were married, with 43.8% attaining secondary education and 25.4% tertiary education. More than half (59.7%) of the respondents were engaged in trading and 14.4% practiced crop farming. Major sources of information on liquid fertilizer were fellow farmers (81.6%), radio (64.7%), and agro-dealers (55.2%), indicating that informal and interpersonal channels play a dominant role in technology dissemination. The logit regression analysis revealed that farm size (P<0.05), membership of cooperatives (P<0.05), and access to extension services (P<0.01) were negative and significantly influenced adoption of liquid fertilizers. On the other hand, access to credit facilities (P<0.05) had a positive and significant influence on adoption of liquid fertilizer. The study concludes that socio-institutional factors such as cooperative membership, credit access, and extension support play critical roles in enhancing adoption of liquid fertilizer. It recommends that agricultural policies focus on strengthening cooperatives, improving access to affordable credit, and revitalizing extension services to promote efficient and sustainable use of liquid fertilizers among maize farmers.